Email von Georgina Beier - Beier, Georgina (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2015)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Art; Africa; Artists; Exhibitions; Music; Art Exhibition; Email; Nigeria; New Zeland; Cultural Centre; Performing Arts Center; Art Collector; Art Collecting